Impact of early mobilization on length of stay after primary total knee arthroplasty - Yakkanti, Ramakanth R.; Miller, Adam J.; Smith, Langan S.; Feher, Anthony W.; Mont, Michael A.; Malkani, Arthur L. (Annals of Translational Medicine, 2019)
Background: Decreasing length of stay (LOS) following primary total knee arthroplasty (TKA) has been an important focus by all the stakeholders involved in the delivery of care. LOS is dictated by both the patient and hospital-related factors. The purpose of this study was to determine if early mobilization on post-operative day 0 (POD 0) following primary TKA has an effect on hospital LOS and discharge to home vs. rehabilitation facilities. Methods: An analysis was performed of consecutive primary TKAs performed at a single institution over one year. Patients were assigned to two groups: POD 0 or POD 1, based on their day of mobilization. Patients were mobilized following surgery based on time of arrival to the orthopaedic floor and availability of physical therapy (PT) resources. The two groups were compared for LOS and discharge disposition using univariate analysis. A total of 408 consecutive TKAs were evaluated and from this group, a total of 143 patients who were mobilized on POD 0 were then matched to 143 patients mobilized on POD 1. There were no significant differences in age, sex, American Society of Anesthesiologists score, or body mass index (BMI) between POD 0 and POD 1 groups. Results: There was a significant difference in LOS between POD 0 and POD 1 groups, 2.44 vs. 2.80 days (P=0.002). There were also differences in discharge to home vs. rehabilitation, 70.63% of the POD 0 cohort were discharged home compared to 58.74% in POD 1 (P=0.035). Conclusions: There was a significant reduction in LOS and there were differences in discharge disposition between patients who mobilized on POD 0 vs. POD 1, with more patients mobilized on POD 0 discharged home. Hospitals should work with their total joint arthroplasty programs to mobilize close to 100% of the patients undergoing primary TKA on POD 0 in order to decrease LOS and healthcare expenditure.